Seven new species of Strongylophthalmyia Heller, 1902 (Diptera: Strongylophthalmyiidae) from the Eastern Palaearctic and Oriental Regions with notes on peculiar rare species - Galinskaya, Tatiana V.; Shatalkin, Anatoly I. (Zootaxa, 2018)
Seven species of Strongylophthalmyia are described as new species: Strongylophthalmyia armipes n. sp. (Malaysia), S. biloba n. sp. (Indonesia), S. bukittinggiana n. sp. (Indonesia), S. minutissima n. sp. (Thailand), S. prominens n. sp. (Vietnam), S. strigosa n. sp. (China), S. vichrevi n. sp. (Russia). New data on morphology and distribution of S. bifasciata Yang et Wang 1992 and S. malayensis Evenhuis, 2016 are provided.